Hubungan Akal dan Hati Dalam Al-Qur’an - Muliani, Nur; Ahmatnijar, Ahmatnijar (Jurnal El-Thawalib, 2022)
The Qur'an is the word of Allah SWT for all mankind which contains knowledge, so to obtain it, humans need to think. Calls for research and thinking activities have been reiterated in the Qur'an with various words such as ta‘qiluun, tafakkara, tafaqqahun and others. However, in the surah al-A'raf verse 179 mentions the heart combined with the word faqiha (yafqahuun), giving the meaning that the heart functions to understand something, this shows the existence of a thought process through the heart and mind. The formulation of the problem of this research, what is the meaning of the words يَفْقَهُوْنَ and قُلُوْبٌ in the Qur'an surah al-A'raf verse 179 and how is the relationship between the mind and heart in the surah al-A'raf verse 179. The aim is to know the relationship between reason and heart. heart, then humans should be able to use it according to His will. This research is a library research, the primary data source is the Qur'an and the book of interpretation, while the secondary data sources are books and scientific works related to research. The conclusion of this research is that in the Qur'an surah al-A'raf verse 179, it shows that there is a combination of heart and mind in the process of working in the human body. Through this combination, healthy humans will be formed and their spiritual potential will be nurtured so that they can relate to Allah SWT and other creatures correctly according to commendable morals by applying them in social life.